Safety of reproduced pharmaceuticals and legal issues of their circulation in Russia - Alexander V. Savoskin; Vitaly A. Rukoleev (RUDN Journal of Law)
Due to restrictions on importing medicines from abroad, the domestic pharmaceutical industry is shifting its focus towards the development and manufacturing generic drugs - medications containing a pharmacological substance identical to the original (previously patented/registered). However, the issue of drug interchangeability remains a subject of debate in both scientific circles and practical applications. Bioequivalence studies often raise concerns due to disparitites in therapeutic effects, posing a high risk of adverse reactions and symptoms. The authors aim to establish a comprehensive understanding of the feasibility and safety of introducing generic drugs in the Russian Federation. To achieve this goal, they utilize a range of general scientific cognitive methods, including analysis, synthesis, induction, deduction, and generalization, as well as systemic, logical-semantic and dialectical approaches. Special legal methodologies, such as formal legal, comparative legal and technical legal analyses, are also employed. It has become evident that generic drug safety and effectiveness in Russia are not subject to thorough evaluation. Analogues are entering the market without undergoning essential therapeutic equivalence assessments, leaving their specific pharmacological properties merely a matter of speculation. The study concludes that while maintaining the balance in the pharmaceutical market through generic drugs is essential, it must be executed with caution. Balancing public interests in replacing foreign drugs with domestic alternatives must be done in harmony with private interests. The authors advocate for a judicial practice that prioritizes individual patient rights, regardless of the country of origin of the drug, since restrictions on the rights of drug’s country of origin, as limiting citizens’ access to medically necessary drugs - domestic or foreign - undermines the fundamental right to healthcare.